Leposoma osvaldoi Avila-Pires, 1995 (Squamata: Gymnophthalmidae): New records and distribution map in the state of Mato Grosso, Brazil - Ricardo Kawashita-Ribeiro; Luana Arruda; Marcos Carvalho; Anelise Silva; Jacqueline Silva; Robson Ávila; Drausio Morais; Tamí Mott (Check List, 2011)
The present study provides the distribution map and reports new records of the gymnophthalmid lizard Leposoma osvaldoi Avila-Pires , 1995, from Mato Grosso state, Brazil, extending the known geographical distribution of the species ca. 42 km northeastern in straight line from the nearest record in the state.